Epidemiology of Positive Blood Cultures due to Multidrug-Resistant Organisms From an Academic Center and Community Hospitals. (October 2020) - Boly, Frances; Olsen, Margaret; Stwalley, Dustin; Burnham, Jason; Kwon, Jennie
Abstract : Background: Multidrug-resistant organisms (MDROs) are a threat to public health. The objective of this study was to define risk factors and outcomes of patients with positive blood cultures due to MDROs in 2 rural community hospitals as compared to a tertiary-care academic center. Methods: Retrospective cohort study with IRB approval from 1 tertiary-care academic center and 2 rural community hospitals (Barnes-Jewish [BJH], Parkland Health Center, and Missouri Baptist Sullivan Hospital) from July 1, 2013, to August 1, 2018. Demographics, comorbidities, procedures, outcomes, and blood and urine culture data were collected from the BJH informatics database for hospitalized patients with positive blood cultures due to MDROs. MDROs were defined according to European and US CDC standards. Results: Of the patients with positive blood cultures growing organisms with the potential to be MDR, 1, 065 (55%) blood cultures grew MDROs from the academic center and 157 (33%) grew MDROs from the 2 community hospitals ( P < .0001). Among these, methicillin-resistant Staphylococcus aureus (35% at BJH and 37% at community hospitals) and MDR Enterobacteriaceae (29% at BJH and 36% at community hospitals) were the most common organisms grown from blood cultures at all hospitals. Among patients with positive MDRO blood cultures, 60% were males and 69% were white, with a mean age of 58 years at BJH. At the community hospitals, 47% were male and 99% were white, with a mean age of 66 years. The most common comorbidity in patients with MDRO bacteremia at BJH was cancer, compared to diabetes at the community hospitals. At all hospitals, >33% of patients with MDRO bacteremia required an ICU stay. Also, 17% of patients with MDRO bacteremia at BJH died during hospitalization compared to 4% at the community hospitals. Among individuals with positive MDRO blood cultures, 9% had a matching isolate from a urine culture at BJH and 46% had a matching urine isolate at the community hospitals. Conclusions: At an academic medical center, the most common organisms identified in MRDO-positive blood cultures included MRSA, MDR Enterobacteriaceae, and VRE. However, at the community hospitals, MRSA, MDR Enterobacteriaceae, and ESBL Enterobacteriaceae were most common. Patients with a positive MDRO blood culture were more likely to have a matching isolate from urine culture at a community hospital compared to the academic center. Further research is needed regarding risk factors and interventions to prevent, detect, and treat MDRO infections. Funding: None Disclosures: Margaret A. Olsen reports consulting fees for contract research from Pfizer, Merck, and Sanofi Pasteur.